2020
DOI: 10.2147/cmar.s238093
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evodiamine Exerts Anticancer Effects Against 143B and MG63 Cells Through the Wnt/β-Catenin Signaling Pathway</p>

Abstract: Background: Osteosarcoma is the most common primary malignant bone neoplasm and is associated with abysmal prognosis. There are limitations of current treatment methods. Therefore, developing new agents to treat osteosarcoma is exceptionally urgent. Aim: This study aimed to evaluate the anticancer effects of evodiamine (EVO) on osteosarcoma cells and, meanwhile, to investigate the underlying mechanisms involved. Materials and Methods: The effect of EVO on the proliferation of osteosarcoma was detected by MTT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Evodiamine is a novel alkaloid, which was isolated from the fruit of Tetradium [32], and it has been considered an effective Chinese medicine for the treatment of gastropathy, hypertension, and eczema [33]. Several studies reported that evodiamine has various biological effects, including anti-nociceptive, anti-bacterial, antiobesity and anti-cancer activities [34][35][36]. However, to date, the effect of evodiamine on the PD-1/PD-L1 axis remains underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Evodiamine is a novel alkaloid, which was isolated from the fruit of Tetradium [32], and it has been considered an effective Chinese medicine for the treatment of gastropathy, hypertension, and eczema [33]. Several studies reported that evodiamine has various biological effects, including anti-nociceptive, anti-bacterial, antiobesity and anti-cancer activities [34][35][36]. However, to date, the effect of evodiamine on the PD-1/PD-L1 axis remains underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Berberine should be combined with Evodiamine to achieve the synergistic effect and improve the antiproliferative and anti-migratory properties against colon cancer cell malignant transformation by modulating TGF-β1 expression. The combination regulates differentiation of colon epithelial cells by downregulating miR-42 and suppressing activity of TGF-β/Smad signaling 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EVO suppresses cancer growing by eliminating stemness and inhibiting invasion and migration (7,31). This is mainly due to the downregulation of epithelial-mesenchymal transition (EMT) (32)(33)(34). For instance, EVO elevated epithelial marker E-cadherin and reduced the expression of mesenchymal markers N-cadherin and vimentin (33), as well as matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9) protein levels (32).…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly due to the downregulation of epithelial-mesenchymal transition (EMT) (32)(33)(34). For instance, EVO elevated epithelial marker E-cadherin and reduced the expression of mesenchymal markers N-cadherin and vimentin (33), as well as matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9) protein levels (32). Many in vitro and in vivo studies had reported beneficial effects of EVO against tumor, and as far as we know, this is the first meta-analysis that assessed the anticancer effect of EVO in preclinical experiments.…”
Section: Discussionmentioning
confidence: 99%